Understanding the needs and challenges of unpaid carers caring for someone with drug and alcohol dependency: findings from a national qualitative evaluation - Sarah Tickle; Sarah Greenhow (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The cost-of-living crisis witnessed in the UK, in addition to the repercussions of the COVID-19 pandemic, has exacerbated growing concerns about its disproportionate impact on caregivers. All caregivers face unprecedented challenges, but this is further intensified when caring for someone with drug and alcohol dependency which this paper argues are direct social harms. Methods This paper presents findings from an external evaluation of three projects from a wider national programme funded by NHS England and Improvement [NHSE/I]. Identified by NHSE/I as a vulnerable community, interviews were conducted with eight caregivers who were caring for someone with drug and alcohol dependency, which this paper focuses on. Results After thematic analysis was conducted on qualitative data, key themes emerged that emphasized a range of specific challenges faced by unpaid carers, including stigmatization and marginalization, a lack of understanding about drug and alcohol dependency, and caring for complex needs, which were particularly challenging in accessing appropriate support. Conclusions Caregivers overwhelmingly advocated for the urgent need to raise awareness around the role of being a “carer,” to see more individualized support provided, in addition to the recognition of treating mental health alongside drug and alcohol dependency in a supportive holistic approach.